Development of radio-frequency (RF) radiation prediction tool and its application - Nurul Izzah binti Sidek (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
The continuous growth of wireless base stations (BS) in the recent years has raised public awareness and concern on the potential health hazards due to exposure to electromagnetic (EM) field or radio frequency radiation (RFR). A tool that can predict and analyze the RFR levels is therefore useful and practical, especially when there are too many sites to be assessed. Current publicly RFR prediction software shows limitations such as lack of display features, no database for easy data interpretation and review. In this thesis, the development of the RFR prediction tool is proposed and shown. Its implementation involves an integration of two RFR prediction models; far-field and near field model into a geographic information system (GIS) software, SAGA GIS with C++ environment and SQL Database Server 5.2. The proposed tool is capable in estimating and visualizing the RFR levels from a single base station in earth as well as for multiple BS simultaneously. The accuracy of the RFR estimation using the proposed tool is compared to a measurement report done by Malaysian Communication and Multimedia Commission (MCMC) in Jalan Pinggiran, Batu Caves for three frequency bands. Using the BS data provided by MCMC, the difference of the cumulative electric field level estimated using the proposed tool ranges from 3.96% up to 58.29% than the true measured signal in all locations. The RFR calculation and performance of the proposed tool is also compared to ITU's RFR prediction software, EMF-Estimator. RFR from an antenna model is estimated in both tools and comparison shows that the variation between the maximum peak between both values in the proposed tool and EMF-Estimator is around 0.485 mW/m2 or 5.623% difference. The advantage of the proposed tool over EMF-Estimator is the ability to display the RFR estimation in the intended directions for 360° azimuth and elevation angles. It also displays the safety distance of the simulated BS to give recommendation on the new placement of another BS in a free space environment. The integration of database management for data storage and updates of the RFR levels are also featured in the proposed tool for efficient RFR monitoring.